Evaluation of the audible noise level on distribution transformers using the Sound Pressure Method - Mina-Casaran, Juan David; Navas, Diego Fernando; Echeverry Ibarra, Diego Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper presents the results of audible noise measurements on ten no-load distribution transformers, using the sound pressure method. The tests were conducted in the Audible Noise Laboratory of Universidad del Valle, according to the requirements described in the Colombian Technical Standard NTC 5979. The tests allowed to verify the conformity of the product in respect with the audible noise limits established in the Colombian Technical Standard NTC 5978. In addition, it was possible to identify the effect on noise emissions of two transformers after variating the voltage in the power source. Results show that the noise level emitted by the transformers under test was considerably lower than the limits established in the standard, and was significantly affected by the voltage of the source supply.